Changing Institutional Leadership in Islamic Schools as a Spark for the Development of Religious Values - Hamiul Fauzah; Mohammad Fajar Faizi (Al-Qalam Institute, 2024)
This study analyses forming religious values ​​in the context of leadership change in Madrasah Ibtidaiyah. This study is based on the importance of leadership in maintaining religious values ​​in Islamic educational institutions, especially during the leadership transition period, which often raises organizational challenges. This study uses a qualitative and case study approach to explore phenomena. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion-drawing steps. This study focuses on educational institutions' strategies, roles, and internal support in maintaining religious values. The study results indicate that leadership has a crucial role in maintaining and developing religious values; strategies used to maintain religious values ​​involve preserving existing traditions and implementing religion-based programs; support from teachers and staff plays a significant role in realizing a sustainable religious environment. The study's results are expected to contribute to developing effective leadership models in Islamic educational institutions, especially in structural change, and enrich the literature on education based on religious values.